Combining strength and endurance training: Molecular bases and applications - Hoppeler, H.; Vogt, M. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
Competitive alpine skiing demands a very high muscle power output over the race duration of 45 to 150 seconds. Required power output is by far in excess of sustainable power levels, hence there is a decline of muscle function, in particular a decrease of available muscle strength, over the course of the race. It would thus seem that it would be of advantage to have the capability of a very high initial power output combined with the capacity to maintain this power output as long as possible over the duration of the race. The latter is in part related to the oxidative capacity of muscle tissue.